Influence of Heterodera glycines Virulence Phenotypes on the Performance of Nematode-Protectant Seed Treatments - Barizon Jefferson; Bissonnette Kaitlyn; Biggs Meghan; Haafke Alexandria; Bish Mandy (Journal of Nematology)
Soybean cyst nematode (SCN; Heterodera glycines) is a major pathogen of soybean (Glycine max) in North America. Although nematodeprotectant seed treatments can complement SCN-resistant soybean varieties in managing this pathogen, their efficacy across different SCN virulence phenotypes remains unclear. This study evaluated whether SCN phenotype influences seed treatment performance and assessed treatment effects on SCN reproduction under controlled conditions. Seeds of the SCN-resistant variety P37A27X (PI 88788) were treated with a base fungicide and insecticide, or the base combined with Aveo EZ (Bacillus amyloliquefaciens); Bio ST (heat-killed Burkholderia rinojensis); Clariva PN (Pasteuria nishizawae); ILEVO (fluopyram); Saltro (pydiflumetofen); or Trunemco (cis-jasmone and B. amyloliquefaciens). Untreated resistant and susceptible seeds served as controls. One non-virulent (HG type 0) and two virulent (HG types 2.5.7 and 1.2.5.7) phenotypes were tested, and treatments were evaluated 30 days after planting. Base-and-ILEVO treatment reduced the population of SCN females by 29% to 72% across phenotypes, and also reduced root mass by 28%, indicating early phytotoxic effects.